L'approche écosystémique de la santé des populations : le cas de l’exposition au mercure des communautés riveraines de l’Amazonie et du nord du Québec - Sebastian Weissenberger; Delaine Sampaio da Silva; Roger Schetagne (Développement Durable et Territoires)
The environmental mercury issue is complex and the subclinical impacts of a long-term exposure to low concentrations have often failed to be taken into account. We discuss two case studies, the Brazilian Amazon and northern Quebec, which figure amongst the best studied cases of mercury exposure. Although the biophysical, geographical and ecological context is quite different, there are notable similarities in the mobilization and transformation of mercury in the ecosystems and in the human exposure. In both cases, changes in land uses play a major role in mobilizing soil mercury. Despite marked differences in the characteristics of the exposed populations and in the scale of the projects, a remarkable convergence in the socio-sanitary approach to the mercury exposure problem can be witnessed. The ecosystem approach, whether implicitly or deliberately adopted, emerges as the best adapted model for this type of environmental issue, especially when paired with a strong implication of the concerned populations. In the absence of any options to reduce the mercury contamination in the affected ecosystems, the emphasis has been put on monitoring and on the management and communication of health risks. The main strategy in order to reduce the population’s exposure to methylmercury has been to influence people’s diet, without discouraging the overall consumption of fish, which has numerous health, economic and social benefits. Great similarities can be observed in the communication tools and strategies used in the two projects, with minor differences arising from the specific situations of local populations. In both regions, a decrease in mercury exposure over time has been observed, but not necessarily for the same reasons. The analyzing of the unfolding and success of the intervention must include the socio-political, cultural and historical context in which they take place. The study of mercury exposure thus offers valuable insights that can be applied to other types of contaminants, but also raises a number of questions of a biogeochemical, health and social nature, which will need to be addressed in the future.